Multiscale investigation of mechanical degradation in Ti3C2O2 assemblies and its Mitigation via black phosphorus integration - Siliang Yue; Hui Qi; Chenliang Li; Jing Guo; Zhe Wang (Materials & Design)
MXene, with their promising potential for a wide range of applications, have garnered significant attention in recent years. However, the tensile strength of Ti3C2O2 after assembly decreases by two orders of magnitude compared to the theoretical value. Therefore, understanding how the internal structure at different scales affects the overall mechanical properties of Ti3C2O2 assemblies is crucial for expanding their application potential. In this study, we employ multiscale modeling based on actual microstructures to investigate the mechanical degradation mechanisms of Ti3C2O2 assemblies across scales, effectively linking microscale features to macroscale mechanical properties. The results reveal that single-layer defects, wrinkling caused by multilayer interactions, and visible damage are the primary factors contributing to the degradation of mechanical properties. Specifically, interlayer wrinkling-induced stress concentrations play a crucial role in strength reduction, while the size and location of voids and cracks within the material determine the upper strength limit. Based on these simulation results, we propose an effective strategy to enhance the material’s performance by incorporating black phosphorus. The addition of black phosphorus significantly strengthens interlayer adhesion, improving the overall structural stability. This modification alleviates stress concentrations and enhances fracture resistance, providing a promising approach to mitigating mechanical degradation in Ti3C2O2 assemblies.